Pengaruh Cara Pengolahan Tanah dan Pupuk Limbah Cair Tahu terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L.) - Asep Sunandar; Islan Islan; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of the interaction of soil treatment methods and tofu liquid waste fertilizer on the growth and yield of soybean plants and get the best combination of treatments. This research was carried out at the University of Riau's Faculty of Agriculture's Technical Implementation Unit (UPT) for 4 months from April to July 2018. The study was conducted experimentally in a 3 x 4 factorial form arranged according to a completely randomized design (RAL). The first factor is the method of tillage consisting of three levels: no tillage (TOT), minimum tillage and perfect tillage. The second factor is the dose of tofu liquid waste consists of four levels: 0 ml.2m-2, 250ml.2m-2, 500 ml.2m-2 and 750 ml.2m-2. The parameters observed were plant height, flowering age, harvest age, number of pods per plant, number of pithy pods per plant, weight of 100 seeds and dry seed production. Soil processing can accelerate flowering age and harvest age, increase the number of pithy pods per plant and dry seed production of soybean plants. Tofu wastewater fertilizer can increase plant height, accelerate flowering age and weight of 100 soybean seeds. Keywords: tillage, tofu liquid waste, soybeans